The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/genes11101150
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Tissue Transcriptome Analysis Identifies Key Sexual Development-Related Genes of the Ornate Spiny Lobster (Panulirus ornatus)

Abstract: Sexual development involves the successive and overlapping processes of sex determination, sexual differentiation, and ultimately sexual maturation, enabling animals to reproduce. This provides a mechanism for enriched genetic variation which enables populations to withstand ever-changing environments, selecting for adapted individuals and driving speciation. The molecular mechanisms of sexual development display a bewildering diversity, even in closely related taxa. Many sex determination mechanisms across an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…GPCRs are characterized by seven transmembrane domains, an external N-terminal domain, and a C-terminal cytosolic domain (25). These are divided among three large classes: rhodopsin-like (Class A), which represents the largest number of GPCRs; secretinlike (Class B); and metabotropic glutamate (Class C) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: G Protein-coupled Receptor-mediated Signalingmentioning
confidence: 99%
“…GPCRs are characterized by seven transmembrane domains, an external N-terminal domain, and a C-terminal cytosolic domain (25). These are divided among three large classes: rhodopsin-like (Class A), which represents the largest number of GPCRs; secretinlike (Class B); and metabotropic glutamate (Class C) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: G Protein-coupled Receptor-mediated Signalingmentioning
confidence: 99%
“…In ornate spiny lobster (Panulirus ornatus), Sxl and Tra-2 isoform-encoding transcripts showed broad tissue expression, with no clear bias between males and females, suggesting that Sxl-Tra-Dsx may be unique to Drosophilidae and not conserved among decapods. However, the male-specific iDMY was conserved between the eastern (Sagmariasus verreauxi) and ornate spiny lobsters (P. ornatus), indicating a conserved central function in sex determination (Ventura et al, 2020).…”
Section: Sex Determinationmentioning
confidence: 98%
“…An insulin family-based signaling system has been proposed based on the structure similarity of IAG to the insulin/IGF family (Sharabi et al, 2016). Several peptide receptors including tyrosine kinase insulin receptor (TKIR), G-protein-coupled receptor (GPCR), insulin receptor (IR), and insulin-like growth factorbinding peptide (IGFBP) have been identified to be the receptor for IAG (Rosen et al, 2010;Aizen et al, 2016;Chandler et al, 2017;Jiang et al, 2020c;Ventura et al, 2020).…”
Section: Downstream Mechanisms Of Sex In Male Decapodsmentioning
confidence: 99%
“…Unlike in insect species, the dsx function is known to be regulated via sex-biased expression (with the majority of cases in males) rather than alternative sex-specific splicing in non-insect arthropods such as the crustacea (details in following sections) and chelicerata (including the common house spider) [ 47 ]. Moreover, in addition to dsx genes, the invertebrate Y-chromosome-linked iDMY genes have recently been identified as a masculinization factor during embryogenesis in the Eastern spiny lobster Sagmariasus verreauxi [ 48 ] and in the ornate spiny lobster Panulirus ornatus [ 49 ]. High-throughput next generation sequencing techniques have successfully enabled the decoding of draft genomes in many Malacostracans ( Table 1 ).…”
Section: Sex Determination and Differentiation Mechanisms In Crustmentioning
confidence: 99%
“…Especially genome information of following species: the marbled crayfish Procambarus fallax f. virginalis [ 26 ], the Pacific white shrimp Litopenaeus vannamei [ 22 ], the giant freshwater prawn Macrobrachium rosenbergii [ 24 ], and the terrestrial isopod Armadillidium vulgare [ 29 ], will accelerate sex determination and differentiation studies, since they have been used in the studies of endocrinology and sex differentiation as experimental animals (details in following sections). Moreover, several transcriptome studies have revealed the existence of female- or male-biased genes in various decapods, shedding light on the understanding of molecular mechanisms underlying sex determination, sexual differentiation, and sexual maturation [ 48 , 49 , 50 , 51 , 52 , 53 ]. Improving the sequencing depth and algorithm for de novo assembly will help to identify the loci of sex-determining genes on sex chromosomes.…”
Section: Sex Determination and Differentiation Mechanisms In Crustmentioning
confidence: 99%